2020
DOI: 10.1039/d0nj00457j
|View full text |Cite
|
Sign up to set email alerts
|

Zr-Based MOFs as new photocatalysts for the rapid reduction of Cr(vi) in water

Abstract: The hydroxyl modified Zr-based MOFs is used for photocatalytic reduction of hexavalent chromium existing in wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…After 60 min of adsorption equilibrium in 20 mg·L –1 Cr­(VI) aqueous solution, DGIST-1­(H 2 ) exhibited pH-dependent catalytic activity where photocatalytic efficiency was obviously enhanced with the decrease of pH (Figure a). This situation is also consistent with the previously reported literature. Control experiments in photocatalysis revealed that Cr­(VI) cannot be reduced in the absence of MOFs or in the dark condition. Based on the optimal condition of pH = 1, sonophotocatalytic Cr­(VI) reduction was performed over DGIST-1­(H 2 ) by adding the ultrasonic wave (60–120 W, 20 kHz) into the abovementioned photocatalytic system (Figure S7).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…After 60 min of adsorption equilibrium in 20 mg·L –1 Cr­(VI) aqueous solution, DGIST-1­(H 2 ) exhibited pH-dependent catalytic activity where photocatalytic efficiency was obviously enhanced with the decrease of pH (Figure a). This situation is also consistent with the previously reported literature. Control experiments in photocatalysis revealed that Cr­(VI) cannot be reduced in the absence of MOFs or in the dark condition. Based on the optimal condition of pH = 1, sonophotocatalytic Cr­(VI) reduction was performed over DGIST-1­(H 2 ) by adding the ultrasonic wave (60–120 W, 20 kHz) into the abovementioned photocatalytic system (Figure S7).…”
Section: Resultssupporting
confidence: 93%
“…At the same time, the samples of DGIST-1­(H 2 ) after the reaction were detected by the XPS measurement. As shown in Figure b,c, the characteristic peaks at 587.7 and 577.5 eV corresponding to the Cr 2p 1/2 and Cr 2p 3/2 orbitals were observed, which correspond to Cr­(III) species, further proving the transformation of Cr­(VI) to Cr­(III). , In addition, according to previous reports, in the absence of any electron sacrifice in the system, the main oxidation product is H 2 O 2 and it can be detected by using N , N -diethyl-1,4-phenylenediamine/horseradish peroxidase (DPD/POD). ,, Because of the low concentration of H 2 O 2 presented in the reaction solution, a small amount of the reaction solution was employed to repeatedly rinse the catalyst to obtain the detection solution. It is observed from Figure d that the mixed solution displayed two absorption bands at 510 and 551 nm, while it is barely observed in the blank; so it is demonstrated that the oxidation product of water is H 2 O 2 .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…[13][14][15] Among them, the reduction of Cr(VI) to Cr(III) by semiconductor photocatalysis is a very effective strategy due to the low toxicity of Cr(III). [16][17][18] Furthermore, tetracycline hydrochloride (TC-HCl), as one of the most common antibiotics, is widely used in various industries such as medicine, agriculture, and animal husbandry. TC-HCl is abundant in the environment due to its stable chemical structure and non-biodegradation, which has already imperiled the ecosystem and human health.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] At present, a common treatment method of Cr(VI) in wastewater is to convert toxic Cr(VI) to less toxic trivalent chromium Cr(III) by means of a variety of techniques including ion exchange, 12 chemical precipitation, 13 membrane separation, 14 biodegradation 15 and photocatalytic technology. 16 Thereinto, photocatalysis with the merits of environmental friendliness, low toxicity and directly using solar energy has become a preferable and cost-effective route for the treatment of Cr(VI) in wastewater. [17][18][19] The key issue is to develop efficient heterogeneous photocatalytic materials.…”
Section: Introductionmentioning
confidence: 99%